Benchmarking of the Transport Market with Hierarchical Clustering of Rail Companies - I.Zorina, O; V.Neskuba, T; M.Mkrtychyan, O; A.Volokhov, V (International Journal of Engineering and Technology, 2018)
The article deals with the hierarchical clustering of operating rail national companies as the main stage of the benchmarking of Europeâ€™s rail transport market, which was proposed for the first time. It was established that at Euro integration the results of taxonomy make it possible to determine efficient areas of cooperation and provide a sufficient competitive level in the rail industry both for European counties and Ukraine. And an optimal criterion for cluster analysis, as was established, is the efficiency indices. Hence, the basic result in hierarchical clustering is division of rail companies into groups with similar performance characteristics. It will allow revealing the main competitors in the industry for each company on the basis of technical, geographic and economic conditions in a particular country. Detailed research of clusters with the k-means method made it possible to obtain more detailed information on characteristics of division and influence of factors on clusters. For accurate identification of characteristics for each cluster a single-factor dispersion analysis was performed. The analysis established the average value of an indicator for the clusters, standard deflection, maximal and minimal values. This information is required for development of the priority areas to improve the operating efficiency and ensure a sufficient competitive level in the rail industry of the EU countries. Â Â